Implementation of Madrasah Diniyah as Strengthening Islamic Education Curriculum at SD Khazanah Ilmu - Mohamad Rojii; Istikomah Istikomah; Hidayatulloh Hidayatulloh (Proceedings of The ICECRS, 2020)
Islamic religious education is one of the most important subject matter that must be obtained by every student in school, but in fact the implementation of Islamic religious education in Indonesia still gets a lot of criticism from various parties, these criticisms regarding the curriculum, learning methods and also to teachers Islamic religious education itself, on the other hand there is one non-formal institution called madrasa diniyah that specifically provides Islamic religious education to the community, this institution can also be integrated with various formal institutions under the umbrella of the education service. if the existence of madrasa diniyah can be utilized to the maximum, it is not impossible that various problems in Islamic religious education can be overcome. The purpose of this research is to examine the pilot school that integrates madrasa diniyah into basic educational institutions as an effort to strengthen the Islamic religious curriculum, namely SD Khazanah Ilmu. This research includes qualitative research, data collection is done by collecting documents, conducting interviews, and also observing at the research site, while the data analysis technique is done by data reduction, data presentation, and drawing conclusions. The results of this study state that the form of implementing madrasah diniyah as a curriculum for Islamic religious education curriculum in the elementary school of science is through several efforts, namely the formulation of the main objectives, the formulation of teaching materials, the system of teaching recruitment based on religious competence, the development of learning methods and techniques, and finally is to carry out routine evaluation programs both daily, weekly, monthly to yearly. All of these efforts are based on one main goal, namely the strengthening of Islamic religious education curriculum in SD Khazanah Ilmu.